Sulfilimines as versatile nitrene transfer reagents: facile access to diverse aza-heterocycles - Tian, Xianhai; Song, Lina; Rudolph, Matthias; Rominger, Frank; Oeser, Thomas; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2019)
We herein report the unprecedented synthesis of diverse biologically important aza-heterocycles by employing sulfilimines as nitrene transfer reagents. This class of sulfur-based aza-ylides had not been successfully used for gold nitrene transfer before. This work contains an efficient generation of α-imino gold carbenes by N−S cleavage of sulfilimines. These gold carbenes undergo C−H insertion, cyclopropanation, and nucleophilic attack to form indoles (44 examples), 3-azabicyclo[3.1.0]hexan-2-imines (24 examples), and imidazoles (3 examples). Our study represents a unique gold-catalyzed reaction between alkynes and sulfur ylides, and also includes the first aza-heterocycle synthesis that proceeds by intermolecular nitrene transfer followed by cyclopropanation of the α-imino gold carbenes. Moreover, an unexpected synthesis of 4-acylquinolines (3 examples) from 2-acylphenyl sulfilimines and propargylic silyl ether derivatives by a 1,2-hydride shift onto the α-imino gold carbene and a subsequent Mukaiyama aldol cyclization was discovered.